Delayed school entry and academic performance: a natural experiment. (18th February 2015) - Jaekel, Julia; Strauss, Vicky Yu‐Chun; Johnson, Samantha; Gilmore, Camilla; Wolke, Dieter
<x xml:space="preserve">Abstract</x> Aim Recent reports suggest that delayed school entry (DSE) may be beneficial for children with developmental delays. However, studies of the effects of DSE are inconclusive. This study investigated the effects of DSE versus age‐appropriate school entry (ASE) on children's academic achievement and attention in middle childhood. Method In total, 999 children (492 females, 507 males; 472 born preterm) were studied as part of a prospective population‐based longitudinal study in Germany. Using a natural experimental design, propensity score matching was applied to create two matched groups who differed only in terms of DSE versus ASE. Teacher ratings of achievement in mathematics, reading, writing, and attention were obtained in Year 1, and standardized tests were administered at 8 years of age. Results There was no evidence of a difference in the odds of DSE versus ASE children being rated as above average by teachers in Year 1. In contrast, the standardized mean test scores for DSE children were lower than ASE children's mean scores in all domains (mathematics: B=−0.28 [−0.51 to −0.06)], reading: B=−0.39 [−0.65 to −0.14], writing: B=−0.90 [−1.07 to −0.74], and attention: B=−0.58 [−0.79 to −0.36]). Interpretation DSE did not affect teacher‐rated academic performance. However, missing 1 year of learning opportunities was associated with poorer average performance in standardized tests at 8 years of age. Future research is needed to determine the long‐term effect of DSE on academic achievement.